Contribution of endoplasmic reticulum Ca(2+) regulatory mechanisms to the inflammation-induced increase in the evoked Ca(2+) transient in rat cutaneous dorsal root ganglion neurons - Scheff, Nicole N. (2013)
Persistent inflammation results in an increase in the magnitude and duration of high K(+)-evoked Ca(2+) transients in putative nociceptive cutaneous dorsal root ganglion (DRG) neurons. The purpose of the present study was to determine whether recruitment of Ca(2+)-induced Ca(2+) release (CICR) contributes to these inflammation-induced changes. Acutely dissociated, retrogradely labeled cutaneous DRG neurons from naïve and complete Freund’s adjuvant inflamed adult male Sprague Dawley rats were studied with ratiometric microfluorimetry. Ryanodine only attenuated the duration but not magnitude of the high K(+)-evoked Ca(2+) transient in neurons from inflamed rats. However, there was no significant impact of inflammation on the potency or efficacy of ryanodine-induced block of the caffeine-evoked Ca(2+) transient, or the impact of sarco-endoplasmic reticulum ATPase (SERCA) inhibition on the high K(+)-evoked Ca(2+) transient. Furthermore, while there was no change in the magnitude, an inflammation-induced increase in the duration of the caffeine-evoked Ca(2+) transient was only observed with a prolonged caffeine application. In contrast to the high K(+)-evoked Ca(2+) transient, there was no evidence of direct mitrochondrial involvement or that of the Ca(2+) extrusion mechanism, the Na(+)/Ca(2+) exchanger, on the caffeine-evoked Ca(2+) transient, and block of SERCA only increased the duration of this transient. These results indicate the presence of Ca(2+) regulatory domains in cutaneous nociceptive DRG neurons within which cytosolic Ca(2+) increased via influx and release are highly segregated. Furthermore, our results suggest that changes in neither CICR machinery nor the coupling between Ca(2+) influx and CICR are primarily responsible for the inflammation-induced changes in the evoked Ca(2+) transient.